Surface morphology of In0.5Ga0.5 quantum dots grown using stranski-krastanov growth mode - Didik Aryanto; Zulkafli Othaman; Abd. Khamim Ismail; Amira Saryati Ameruddin (Universiti Kebangsaan Malaysia, 2010)
In this research an atomic force microscopy (AFM) study on self-assembled In0.5Ga0.5As/GaAs quantum dots (QDs) was performed. Surface morphology of self-assembled In0.5Ga0.5As QDs changes with different growth time. Increasing growth time increased the dots size and decreased the dots density. In addiditon, self-assembled In0.5Ga0.5As QDs was grown on In0.1Ga0.9As underlying layer with different after-growth AsH3 flow time during cooling-down. The underlying layer caused lattice strain relaxation in the QDs on the surface. Increasing the period of AsH3 flow during cooling-down reduced the diameter of the dots and increased the density. The migration of groups III species in the growth of In0.5Ga0.5As/GaAs system was influenced by AsH3 flow during cooling-down period. This was due to the increase in surface population of active arsenic species. Underlying layer and the period of AsH3 flow during cooling-down are the two key factors in the fabrication of small and dense In0.5Ga0.5As QDs.